Duchowa interpretacja Biblii w III wieku (na przykładzie dialogu Uczta biskupa Metodego z Olimpu) - Andrzej Siemieniewski (Wrocławski Przegląd Teologiczny)
Pope Benedict XVI in his Adhortatiom Verbum Domini encourages Catholic theologians to take example from the ancient and medieval authors who applied to the Bible interpretation the notion of four biblical senses: literal, allegorical, moral and anagogical (the latter three form the spiritual sense of the Scriptures). This essay is an effort to read an ancient Christian text and to find therein traces of such a theological method. The text chosen to this purpose is the Methodius of Olimpus’ dialogue Banquet of the Ten Virgins written around 300 CE. Ten virgins pronounce their eulogy to the life consecrated to Jesus Christ, abundantly quoting thereby and interpreting the Bible. We see as all ten Christian virgins described in the Methodius’ work read the biblical texts through the lenses of the Church faith. It is especially significant when the lecture of the Old Testament passages is done in the context of the New Testament fulfillment of the salvation history.